Sumber Daya Manusia Dalam Otonomi Daerah - Soeboko, Soeboko; Riyardi, Agung (Universitas Muhammdaiyah Surakarta, 2000)
The failure of the centralized development is solved by replace it with decentralization. The main issue in decentralization is human resources development. In the past, economic development oriented in creating more productive human resources. But, this model failed in its contribution in the process of developing qualified human resources. A new paradigm of human resources development must consider human not only as a production factor but it has to see human from any other aspects. The characteristics of the new paradigm of human resources development, that there are human development and people centered development in the process of human resources development. But, the challenge is how to integrate the existence of religion in the development of the society.